Volatile compounds profiling by using proton transfer reaction‐time of flight‐mass spectrometry (PTR‐ToF‐MS). The case study of dark chocolates organoleptic differences. (17th January 2019) - Deuscher, Zoé; Andriot, Isabelle; Sémon, Etienne; Repoux, Marie; Preys, Sébastien; Roger, Jean‐Michel; Boulanger, Renaud; Labouré, Hélène; Le Quéré, Jean‐Luc
Abstract : Ahhhh chocolate! Who doesn't love chocolate? The analysis of volatile organic compounds (VOCs) emanating from environment, plants, food or food ingredients has been the basis for many studies aiming at categorizing samples or sites. For this purpose, global VOCs profiles may be used as fingerprints of the samples, sometimes referred to as "volatilome". In this special feature, Jean‐Luc Le Quéré and co‐workers use proton transfer reaction mass spectrometry (PTR‐MS) coupled to a time‐of‐flight (TOF) mass analyzer to classify over 200 dark chocolate samples based on their content in VOCs. The final goal was to build a model based on the PTR‐MS monitored dark chocolates volatilome that could be used to predict the four distinct sensory poles previously defined based on the flavor of cocoa from diverse origins and cultivars. Jean‐Luc Le Quéré is a Senior Researcher at the Center for Taste and Feeding Behaviour of the Institut de Recherche Agronomique (INRA) of Bourgogne‐Franche‐Comté (France). The general objective of this center is to get a better understanding of the physicochemical, molecular, cellular, behavioral and psychological mechanisms underlying sensory perception of food, eating behavior and health consequences.